Benzalkonium chloride, benzethonium chloride, and chloroxylenol - Three replacement antimicrobials are more toxic than triclosan and triclocarban in two model organisms. (April 2018) - Sreevidya, Virinchipuram S.; Lenz, Kade A.; Svoboda, Kurt R.; Ma, Hongbo
Abstract: With the recent ban of triclosan (TCS) and triclocarban (TCC) from some personal care products, many replacement antimicrobial compounds have been used. Yet the potential health risk and environmental impact of these replacement compounds are largely unknown. Here we investigated the toxicological effects of three commonly used replacement antimicrobials, benzalkonium chloride (BAC), benzethonium chloride (BEC), and chloroxylenol (CX) to two model organisms, the nematode C. elegans and zebrafish ( Danio rerio ), and compared them to the banned TCS and TCC. We found that these replacement compounds are not any safer than the banned antimicrobials. In the worm, at least one of the three, BAC, showed comparable toxicity to TCS from organismal to molecular levels, with toxic effects occurring at lower hundred μg/L to lower mg/L levels. In the fish, all three compounds at the tested concentration ranges (0.05–5 mg/L) showed toxicity effects to zebrafish embryos, indicated by hatching delay or inhibition, embryonic mortality, morphological malformations, and neurotoxicity. BAC was the most toxic among the three, with acute lethal toxicity occurring at environmentally relevant concentrations (hundreds of μg/L), which is comparable to the banned TCC. However, the toxicity effects of BAC and TCC occurred within different time windows, potentially suggesting different mechanisms of toxicity. CX was the only compound that induced a "body curvature" phenotype among the five compounds examined, suggesting a unique mode of toxic action for this compound. Furthermore, all five compounds except TCS induced neurotoxicity in fish larvae, indicated by alterations in secondary motoneuron axonal projections. Such neurotoxicity has been largely understudied for these antimicrobials in the past years and calls for further investigations in terms of its underlying mechanisms and ecological significance. These findings strongly indicate that scrutiny should be put on these replacement compounds before their introduction into massive use in personal care products. Graphical abstract: Image 1 Highlights: Toxicity of three replacements to triclosan and triclocarban is studied. Benzalkonium chloride shows comparable toxicity to triclosan in C. elegans. All three replacement compounds show greater toxicity to zebrafish embryos. Triclocarban and three replacement compounds induce neurotoxicity in fish embryos. Scrutiny should be put on replacement antimicrobials before their use. Abstract : Three replacement antimicrobial compounds induce comparable toxicity effects with triclosan and triclocarban in C. elegans and greater toxicity effects in zebrafish embryos.